UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PKN MELALUI MODEL PEMBELAJARAN KOOPERATIF EXAMPLE NON EXAMPLES SISWA KELAS I SD NEGERI 012 PANGKALAN BARU KECAMATAN SIAK HULU - Zaitun Zaitun (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The background of this study is the low activity and learning outcomes of Civics students in grade 1 012 SD Negeri 012Pangkalan Baru, for this reason, improvements are made to learning through classroom action research using example nonexample learning models. The purpose of this study is to increase Civic Education activities and learning. This research is aclassroom action research conducted at SD Negeri 012 Pangkalan Baru. The subjects of this study were grade 1 students with 23students. This study was carried out in two cycles, which were carried out in four stages: planning, implementation, observation,and reflection. The results of the study showed that students' learning activities had increased, in cycle 1 meeting 1 in the verygood category got 28.99%, in the good category was 29.13%, in the sufficient category was 31.88%, and in the poor categorywas 10 00%. At meeting 2 in the very good category was 46.38%, in the good category was 31.88%, in the sufficient categorywas 21.74%, and in the less category was 5.00%. In cycle 2 meeting 1 activity in the very good category was 53.62%, in the goodcategory was 33.33%, in the sufficient category was 13.04%, and in the poor category was 4.60%. At meeting 2 in the very goodcategory was 73.91%, in the good category was 18.84%, in the sufficient category was 7.25%, and in the less category was0.00%. In addition, student learning outcomes have increased, in cycle 1 meeting 1 the number of students who completed was18 students (78.26%), at the second meeting reached 21 students (91.30%). In cycle 2 meeting 1 reached 19 (82.61%), and at themeeting of 2 to 20 students (86.96%).